Pendidikan Karakter Berbasis Kearifan Lokal sebagai Solusi Permasalahan Sosial di Kalangan Remaja - Amir, Johar; Nurul Mukhlisah Abdal; Syarifah Fatimah; Ambo Dalle; Rahmat Burhamzah (Jurusan Pendidikan Teknik Elektro, 2025)
Social issues among teenagers such as declining manners, lack of responsibility, weakened sense of tolerance, and poor collaboration reflect an ongoing crisis of character that calls for immediate and thoughtful intervention. This study explores the effectiveness of character education rooted in local wisdom as a meaningful solution to help shape the moral development of adolescents. Using a descriptive qualitative approach within an action research framework, the program was implemented in a public high school located in a culturally rich community where traditional values are still widely practiced. The findings indicate a significant improvement in five key character traits: responsibility (23%), respectfulness (25%), cooperation (24%), tolerance (26%), and discipline (25%). Local values such as gotong royong (mutual cooperation), musyawarah (deliberation), and siri’ na pacce (dignity and empathy) were integrated into the learning process through contextual and collaborative methods. These efforts successfully encouraged students to internalize and apply positive behaviors in their daily lives. This study supports the theories of contextual learning and social constructivism, emphasizing that education grounded in cultural identity not only preserves heritage but also effectively nurtures strong character in young people. In a time of rapid globalization, such an approach proves to be both relevant and transformative.